Effect of Pueraria mirifica subchronic treatments on ameliorating depression by increasing tryptophan hydroxylase immunoreactive neurons via estrogen receptors in ovariectomized mice - Nattawut Tadsaichol; Wandee Udomuksorn; Ekkasit Kumarnsit; Uraporn Vongvatcharanon; Surapong Vongvatcharanon (Penerbit Universiti Kebangsaan Malaysia, 2024)
Estrogen depletion leads to menopause-associated depression. Pueraria mirifica (PM) contains phytoestrogen that has been used for rejuvenating in aged women. Therefore, this study aimed to investigate the effect of PM on depression-like behavior, density of tryptophan hydroxylase immunoreactive (TPH-ir) neurons and intensity of estrogen receptor a (ERa) and b (ERb) in dorsal raphe nucleus (DRN) in ovariectomized (OVX) mice. Adult female IRC mice were divided into 7 groups: (1) Sham-operates (SHAM), (2) OVX and distilled water treated (PM0), (3) OVX and 40 mg/kg estradiol benzoate treated (E40), OVX and ethanolic extract of PM treated for 90 days at various doses (4) 25 mg/kg (PM25), (5) 50 mg/kg (PM50), (6) 100 mg/kg (PM100) and (7) OVX and 20 mg/kg fluoxetine treated for 20 days. The duration of immobility in both the FST and TST significantly prolonged in the PM0 group and significantly shortened in the E40, PM50, PM100, and fluoxetine groups (p<0.05). The density of TPH-ir neurons in the DRN was significantly reduced in PM0 and significantly increased in the E40, PM25, PM50, PM100, and fluoxetine (p<0.05). The ERb immunoreactivity (ERb-ir) was much stronger than the ERα immunoreactivity (ERα -ir). However, the intensity of the ERα-ir and ERb-ir was significantly decreased in the PM0 and PM25 groups and significantly increased in the E40, PM50, PM100, and fluoxetine (p<0.05). Therefore, we suggested that subchronic treatments with 50 mg/kg and 100 mg/kg of PM played an effective role in improvement of depression by stimulating TPH via ERb.